Information Systems Innovation Among Organizations - Swanson, E. Burton (Management Science, 1994)
In an era of revolutionary new developments in basic information technology, innovation in its employment among organizations is increasingly crucial to competitive survival and success. The Information Systems (IS) unit within the business is largely responsible for meeting this challenge. Yet, current theory explains little about IS innovation and its role in organizational innovation in general. We suggest some needed foundations. IS innovations are posited to be of three types: Type I innovations confined to the IS task; Type II innovations supporting administration of the business; and Type III innovations imbedded in the core technology of the business. Diffusion among organizations is conjectured to occur by means of a communication circuit in which each IS unit is linked to its professional and business environments. Systematic differences in adoption and evolution patterns among IS innovation types are expected. Three specific IS innovations—data administration, the information center, and material requirements planning (MRP)—illustrate.